2014
DOI: 10.1097/der.0000000000000078
|View full text |Cite
|
Sign up to set email alerts
|

Barrier Creams

Abstract: Barrier creams (BCs) represent devices aiming to protect the skin from contact with exogenous hazardous substances, especially under working conditions. By preventing penetration and absorption of contaminants, BCs are designed to reduce the risk of developing both irritant and allergic contact dermatitis. In fact, BCs should improve stratum corneum hydration as well as provide emolliency to maintain skin integrity and to restore and repair the epidermis barrier function. The formulation and ingredients of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…The ability of such a formulation to reduce the dermal uptake of Ni can be attributed to some ingredients such as ceramide 3, cholesterol, hydrogenated polydecene, and fatty acids, which are able to form a more resistant lipid film. Moreover, formulation B is a repairing and protective cream for the epidermal barrier, containing a balanced mixture of fundamental lipids of the epidermis such as ceramide 3, cholesterol, and fatty acids able to restore the skin barrier function [58,59] and palmitamide MEA with soothing activity on irritation and itching [60]. These obtained results concerning the effectiveness of such two products to reduce cutaneous Ni penetration are consistent with our previous study [23].…”
Section: Discussionsupporting
confidence: 88%
“…The ability of such a formulation to reduce the dermal uptake of Ni can be attributed to some ingredients such as ceramide 3, cholesterol, hydrogenated polydecene, and fatty acids, which are able to form a more resistant lipid film. Moreover, formulation B is a repairing and protective cream for the epidermal barrier, containing a balanced mixture of fundamental lipids of the epidermis such as ceramide 3, cholesterol, and fatty acids able to restore the skin barrier function [58,59] and palmitamide MEA with soothing activity on irritation and itching [60]. These obtained results concerning the effectiveness of such two products to reduce cutaneous Ni penetration are consistent with our previous study [23].…”
Section: Discussionsupporting
confidence: 88%
“…The emollient acts as a physical barrier to lower the Trans Epidermal Water Loss (TEWL), which provides water content recharge in the corneum stratum, so it requires the use of emollient after washing hands to reduce the increase in dermatitis due to repeated washing of hands in response to COVID-19 8 . The effectiveness of various types of emollients has been studied by other authors; according to Corazza, 2014, emollients have been shown to protect against detergents such as sodium lauryl sulfate (SLS) and hydrophilic substances such as NaOH on wet work, but in a study written in article 9 . Stearate acid contained in the emollient, when reacting with NaOH, can increase irritation and then cause irritant contact dermatitis 9 .…”
Section: Introductionmentioning
confidence: 99%
“…BCs are used to prevent the irritant effect caused by occupational exposure and are recommended for application before and during work. Some authors call them prework creams [8,9,10]. They have also been called ‘invisible gloves' but the term ‘skin protective creams' is more appropriate [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors call them prework creams [8,9,10]. They have also been called ‘invisible gloves' but the term ‘skin protective creams' is more appropriate [10]. The objective of the BCs is to inhibit or delay cutaneous penetration of substances which could have deleterious effects at the time of skin contact or induce systemic effects due to percutaneous absorption [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation